Development of Learning Cycle 5E Oriented Learning Tools to Critical Thinking Skills and Creative Thinking - Endra Priawasana; Abdul Muis (Indonesian Journal of Instructional Media and Model, 2021)
Biology learning can do by exploring the nature and its contents, including living beings an inanimate beings everyday life. In past, students have not active roles process in the classroom. Students are only required to memorize the factual information obtained from the teacher. They should develop their potential broadest in order to understand the processes and concepts that exist. The development potential of students begins by assembling the experience and knowledge that has bebn previously owned. Biology learning is expected to be implemented by the Learning Cycle 5E, so that students are expected to improve the understanding of the experience and prior knowledge. By carring out an Learning Cycle 5E, students will find their own concepts of biology and can develop biology process skills, so as to equip students with skills such as scientists and make them able to solve his problems independently. Students will become more critical in thinking and looking for creative answers to the problems they face in everyday life. By nit dong rote, students are expected to be qualified individual.